ANALYSIS OF STUDENT’S PROBLEM-SOLVING ABILITIES AS AN EFFORT TO IMPLEMENT THE STEM-BASED MICROLEARNING APPROACH - Ekasari, Aprilita; Yuliatun, Tutik (Jurnal Pendidikan Fisika, 2024)
Advancements in science and innovation influence the progress of education in Indonesia. The current situation in Indonesia is characterized by a lack of competent human resources (HR). Quality education helps students develop the values they need for life. The purpose of this research is to describe students' problem-solving abilities so that the implementation of the STEM-based Microlearning approach can yield optimal results. The research will be conducted in the eighth-grade class of Ibn Sina Islamic Middle School. A quantitative descriptive approach is used in this research. A set of 10 problem-solving based descriptive questions is the instrument used in this research. The instrument to be used has been validated. The expert validation results for the questions yielded an average score of 95.33. Data analysis results show that students' problem-solving abilities on the "useful description" indicator obtained an average score of 64%, which can be interpreted as falling into the "good" category. On the "physics approach" indicator, an average score of 64% was obtained, also interpreted as "good." On the "specific application of physics" indicator, an average score of 64% was obtained, which falls into the "good" category. Similarly, on the "mathematical procedures" indicator, the average score obtained by students was 60%, categorized as "satisfactory." Additionally, on the "logical progression" indicator, students obtained an average score of 60%, which can be interpreted as "satisfactory." The research results are used as a reference for further research to improve students' problem solving abilities by developing learning media technology or learning models.